The relationship between inhibition and working memory in predicting children's reading difficulties. (19th July 2013) - Booth, Josephine N.; Boyle, James M.E.; Kelly, Steve W.
<x xml:space="preserve">Abstract</x> The study evaluated the role of working memory and inhibition in predicting children's word reading difficulties. Twenty‐one participants with word reading difficulties were individually matched to two other participants to form the chronological‐age‐matched and the reading‐level‐matched group. All participants were administered measures of performance IQ, inhibition and working memory. Multinomial logistic regression revealed that tasks of working memory and a composite measure of inhibition discriminated between the groups above the impact of performance IQ when the working memory task was verbally based, but only inhibition discriminated when a nonverbal working memory task was used. This suggests domain‐specific deficits on tasks of working memory, independent of the influence of inhibition on reading difficulties. The implications for theory and assessment practice are discussed. Practitioner points What is already known about this topic Children with reading difficulties show impairments with some executive function tasks. Discrepant findings reported in the literature may be related to task modality (e.g. verbal or nonverbal response). What this paper adds Tasks of inhibition and working memory, which required a verbal response discriminated children with reading difficulties from both chronological‐age‐matched and reading‐level‐matched control groups. However, when working memory tasks that placed fewer demands on participants' language skills were used, they did not successfully discriminate between the groups. Executive function task performance was more predictive of reading group membership than general performance measures of cognitive abilities (IQ). Results suggest a deficit with inhibition and verbal working memory, which was not due to slower developing language skills. Implications for practice and/or policy Educational and School Psychologists, Special Educational Needs Advisers and Coordinators, and others engaged in the identification of reading difficulties should consider including tests of inhibition in assessments of executive function.